Interactions Between Plant Hormones Regulate Submergence‐induced Shoot Elongation in the Flooding‐tolerant Dicot Rumex palustris - VOESENEK, L. A. C. J. (Ann Bot, 2003)
Rumex palustris has the capacity to respond to complete submergence with hyponastic (upward) growth and stimulated elongation of petioles. These adaptive responses allow survival of this plant in habitats with sustained high water levels by re‐establishing contact with the aerial environment. Accumulated ethylene in submerged petioles interacts with ethylene receptor proteins and operates as a reliable sensor for the under‐water environment. Further downstream in the transduction pathway, a fast and substantial decrease of the endogenous abscisic acid concentration and a certain threshold level of endogenous auxin and gibberellin are required for hyponastic growth and petiole elongation. Interactions of these plant hormones results in a significant increase of the in vitro cell wall extensibility in submerged petioles. Furthermore, the pattern of transcript accumulation of a R. palustris α‐expansin gene correlated with the pattern of petiole elongation upon submergence.